DAMPAK PENERAPAN PP. NO. 46 TAHUN 2013 TENTANG PAJAK PENGHASILAN TERHADAP UMKM & PENERIMAAN NEGARA - Herawati Khotmi (Valid: Jurnal Ilmiah, 2016)
Since July 1, 2013 entry into force PP. No. 46 of 2013 about income tax on income from business derived by the taxpayer which has a certain gross turnover. based pp No. 46 of 2013 intended to facilitate the calculation, deposits and tax reporting, simplification of tax rules, creating a community for the orderly administration and the transparency of the public. This research aims to determine the impact of the PP. No. 46 of 2013 for SMEs and state revenues. This research uses descriptive method. The results showed in terms of the implementation of the calculation, deposit and agency reporting much simpler and smaller than the amount of tax payable using the old rate before the enactment of PP. No. 46 of 2013. While revenues for the country with the implementation of PP. No. 46 of 2013 increased by 18.20% from the year prior to the enactment of PP. No. 46. With the enactment of PP. No. 46 is good for the taxpayer here,namely CV. Lombi and receiving countries have a positive impact